2017
DOI: 10.1113/ep085949
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ageing on hypoxic exercise cardiorespiratory, muscle and cerebral oxygenation responses in healthy humans

Abstract: What is the central question of this study? This study aimed to determine the effect of ageing on cardiorespiratory and tissue oxygenation responses to hypoxia during maximal incremental exercise. What is the main finding and its importance? Older healthy subjects had preserved hypoxic cardiorespiratory and tissue oxygenation responses at rest and during moderate exercise. At maximal exercise, they had a reduced hypoxic ventilatory response but similar maximal power output reduction compared with young individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Most of the studies involved healthy young adults (between 20 and 39 years old as shown in Figure 4 ). Obviously, the general trends show a progressive decrease in HR max with altitude whatever the age groups, without marked differences (Puthon et al, 2017 ). A trend toward a slightly greater decrease is observed in 30-39 years vs. 20-29 years.…”
Section: Decrease In Hr Max In Acute Hypoxia: a Unmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the studies involved healthy young adults (between 20 and 39 years old as shown in Figure 4 ). Obviously, the general trends show a progressive decrease in HR max with altitude whatever the age groups, without marked differences (Puthon et al, 2017 ). A trend toward a slightly greater decrease is observed in 30-39 years vs. 20-29 years.…”
Section: Decrease In Hr Max In Acute Hypoxia: a Unmentioning
confidence: 99%
“…In Figure 4 , 14-19 years and 50-59 years age groups show different behaviors than 20–29 years and 30–39 years age groups, but likely due to small sample sizes and to the fact that for these ages groups, participants were patients for whom only few data are available (Supplementary Table S1 ). Hence, if HR max decreases with age (Lhuissier et al, 2012 ), age per se does not seem to alter the decrement in HR max with acute hypoxia (Puthon et al, 2017 ), but this needs to be confirmed by specifically designed studies. It also suggests that the hypoxia effects will be relatively greater for an older subject compared to a younger one.…”
Section: Decrease In Hr Max In Acute Hypoxia: a Unmentioning
confidence: 99%
“…However, the majority of studies on obesity and aging have mainly been carried out in Western society, and studies using hypoxic therapy for health promotion of the older adult population are very limited. 3,[14][15][16][17][18] Until now, the majority of obese and aging studies have focused on abdominal or central obesity, hypertension, insulin resistance, high triglyceride and low high-density lipoprotein cholesterol levels, which are associated with metabolic syndrome. 6 The numerous changes in health-related factors that occur during the process of obesity and aging need to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, recently published data suggest that the ventilatory response to hypoxia and hypercapnia at rest and during sub‐maximal effort in elderly subjects (mean age of 66 years) is normal (Puthon et al . ). The automatic ventilatory drive has never been studied in older subjects.…”
mentioning
confidence: 97%
“…It should also be emphasised that their hypothesis that the reduction in the automatic neural drive to breathe is linked to ageing requires more evidence. Indeed, recently published data suggest that the ventilatory response to hypoxia and hypercapnia at rest and during sub-maximal effort in elderly subjects (mean age of 66 years) is normal (Puthon et al 2017). The automatic ventilatory drive has never been studied in older subjects.…”
mentioning
confidence: 99%